A New Approach for Broken Bar Fault Detection in Three-Phase Induction Motor Using Instantaneous Power Monitoring under Low Slip Range - Yassine Maouche; Mohamed El Kamel Oumaamar; Mohamed Boucherma; Abdelmalek Khezzar (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The majority of research is about the detection of broken bar fault in three-phase induction motor at high slip. Thus, it becomes very interesting and demanding to detect faults in case of low slip range. In this study, a novel investigation of broken bar faults using instantaneous power is presented. The method is based on calculations and frequency analysis of partial and total instantaneous power under low slip range. The used model of squirrel cage induction machine takes into account the geometry and winding layout. This model will be used to analyze the impact of broken bar on instantaneous power spectrum. The proposed ideas in this paper are veriﬁed experimentally. The results show that broken bar fault can be more reliably detected under low slip range when using a large frequency area of both partial and total instantaneous power spectrums.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4611